Extraction of Adenosine from Ganoderma lucidum Using Novel Extraction Technologies - Yoswathana, N.; Eshtiaghi, M.N.; Ebadi, A.G. (Asian Journal of Chemistry, 2010)
The aim of this research is to extract adenosine from Ganoderma lucidum (GL) using novel extraction techniques, including high hydrostatic pressure (HHP), ultrasonic assisted extraction (UAE), supercritical carbon dioxide (ScCO2) in comparison with maceration and Soxhlet. The results showed that the highest adenosine extraction could be achieved using HHP (1.86 mg/g dry sample at 2000 bar, 60 ºC sample to solvent ratio of 1:60 and very short extraction time of 5 min) followed by Soxhlet (1.77 mg/g dry sample, 3 h extraction time). The effect of pressure and temperature during supercritical carbon dioxide extraction of adenosine were distinct at pressure higher than 400 bar and moderate temperature (0.40 mg/g dry sample at 500 bar and 60 ºC). The combination of maceration and ultrasonic at moderate temperature (60 ºC) improved the extractability of adenosine up 1.01 mg/g dry sample.